2020
DOI: 10.1002/ardp.202000030
|View full text |Cite
|
Sign up to set email alerts
|

Novel benzo[b]xanthene derivatives: Bismuth(III) triflate‐catalyzed one‐pot synthesis, characterization, and acetylcholinesterase, glutathione S‐transferase, and butyrylcholinesterase inhibitory properties

Abstract: In this study, 3,4‐dihydro‐12‐aryl‐1H‐benzo[b]xanthene‐1,6,11‐(2H,12H)trione compounds were obtained through one‐pot condensation of various substituted aromatic aldehydes, 2‐hydroxy‐1,4‐naphthoquinone, and dimedone in the presence of Bi(OTf)3 as a green and reusable catalyst. The structural characterization of these novel substituted benzo[b]xanthenes was performed by spectroscopic methods, and their inhibitory actions against butyrylcholinesterase (BChE), acetylcholinesterase (AChE), and glutathione S‐transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…All compounds were prepared with the Ligprep module [70] according to the method described in previous studies. [71] Then, the pharmacokinetic properties of the compounds were calculated using the Qikprop module. [72] The structures were made ready for docking studies using the Protein Preparation Wizard module.…”
Section: Bioactivity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All compounds were prepared with the Ligprep module [70] according to the method described in previous studies. [71] Then, the pharmacokinetic properties of the compounds were calculated using the Qikprop module. [72] The structures were made ready for docking studies using the Protein Preparation Wizard module.…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…Binding site prediction and evaluation of the sites were performed according to the method described in previous studies. [71] The induced-fit docking method [76] was tested with the redocking process before the compounds were docked and after molecular docking studies of the most effective compounds were performed using the induced-fit docking module. [71] CONFLICTS OF INTEREST…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…The results of the molecular docking study are similar to those suggesting that the most effective derivative, 2f, of benzimidazolium salts showed π-π stacking interactions between benzene ring moiety and the residues of Tyr 337 and Tyr341. [46] Turhan et al [47] investigated the effects of benzo[b]xanthene compounds and found similar hydrophobic and π-π stacking interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria have been found to produce IAA that may induce root growth directly by stimulating plant cell elongation and cell division or indirectly by ACC deaminase activity 8,10 . Microbes that produce IAA can only promote host plant growth to a certain extent, an excess of which can have negative effects, a trait commonly found in pathogenic microbes 5 .…”
Section: Published By Abasyn Universitymentioning
confidence: 99%
“…Some of the strains of rhizobacteria e.g. Acetobacter diazotrophicus, Rhizobium phaseoli, Herbaspirillum seropedicae, Bacillus cereus, B. macroides, B. licheniformis, and B. pumilus, Burkholderia cepacia SE4, A. chroococcum SE370, and have been known to produce IAA which support plant growth promotion 5,[8][9][10][11] .…”
mentioning
confidence: 99%